Statistical correlations between Standard Penetration Test N value and Pressuremeter modulus for Kallang and Old Alluvium formation - Chia, Pooi Sian (2020)
This paper presents a correlation between the Standard Penetration Test N value and Pressuremeter modulus (Epmt) for Clayey (cohesive) and Sandy (cohesionless soil) in Ang Mo Kio area, Singapore. This study is based on the result of a comprehensive site investigation for future MRT in Singapore. The latest edition of the Singapore Geological Map (DSTA, 2009) indicates that the main Geological Formations at the site is the Kallang Formation and the Old Alluvium. Thus, this study focused on the statistical correlations between SPT- N value and EPMT for Kallang Formation and Old Alluvium with different soil type, such as Sandy Silt, Sandy Clay, Silty Sand, Clayey Sand and Gravelly Sand. The literature review shows that there is very limited or no information available about correlations between Standard Penetration Test N value and Pressuremeter Modulus (Epmt) for Kallang Formation and Old Alluvium. Hence, the relationship between and Pressuremeter Modulus (EPMT) is identified in this study, all the results show a significant linear relationship between SPT-N and EPMT. The results show the increase in the measured SPT-N and Epmt values with greater depth in the soil. The empirical equations between SPT-N value and EPMT are suggested and proposed. In order to verify the empirical equations, the empirical equations obtain from regression analysis in this study have been compared with similar equations and soil type with other researchers. The comparisons indicated that there is a similar linear relationship between researches but the slope (gradient) of linear regression is different. Lastly, comparative study of difference type of pressuremeter system (diameter measuring system and volume measuring system) are carried out. Both measuring systems have more consistency result in Clayey (Cohesive) soil and less consistency result in Sandy (Cohesive) soil. The diameter measuring system has a higher consistency in Sandy (Non-cohesive) Soil whereas Volume measuring system has a less scattered result and higher R2 value in Clayey (Non-cohesive) Soil.